Developing a logic model of change for the determinants of parental nurturance in the first 1000 days: A mixed-method study protocol. - Tessa Goldschmidt; Babatope O Adebiyi; Nicolette V Roman (PLoS ONE, 2021)
Background Parents play a key role in providing nurturance and nurturing care to their child during the first 1000 days which is important for optimal child development. Various factors have been found to influence parenting but the contribution of these factors toward parental nurturance within the first 1000 days is not yet known in the South African context. This paper describes a protocol for a project that aims to develop a logic model of change for the determinants of parental nurturance in the first 1000 days in the South African context. Method This study will apply a mixed methods approach with a sequential design within an intervention mapping framework. The study will occur in two phases. The first phase will identify the problem, which will be done via a scoping review, a policy review and a needs assessment for parents and stakeholders. This phase will recruit approximately 35 participants (20 parents and 15 stakeholders) for the qualitative component and then approximately 398 participants for the quantitative component. Data will be collected via semi-structured interviews and with questionnaires (Home Observation for Measurement of the Environment Inventory, the Depression and Anxiety Scale, and the Multidimensional Perceived Social Support Scale). Data will be thematically analysed, and the Statistical Package for Social Science (SPSS) will be used to determine descriptive statistics, both of which will inform the development of the model in phase 2. The second phase will be the development of a logic model of change for determinants for parental nurturance in the first thousand days. This phase will consist of one stage- a consensus workshop which will be attended by approximately 20 participants (5 parents, 5 pregnant woman/new mothers, and 10 stakeholders). The data collected in this stage will be thematically analysed and will contribute to the refinement of the model. Discussion The first thousand days (FTD) is a period in which rapid growth occurs in all domains of development. If children do not receive sensitive and responsive care in an environment that is conducive for their optimal development, children may not reach their full developmental potential.